Improving High Order Thingking Skills Using Problem Based Learning Models Grade Of SD Negeri 3 Sangub - Bari Setyawan Budi Purnomo (Universitas Sebelas Maret, 2022)
The purpose of this study was to improve the HOTS skills of fifth grade students at SDN 3 Sangub on the theme 2 of animal locomotion through the application of the Problem Based Learning (PBL) model. This type of research is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of several stages, namely planning, implementation of action, observation and reflection. The subjects in this study were fifth grade students at SDN 3 Sangub which consisted of 12 students. The main techniques in data collection were carried out by means of tests and observations, while the supporting techniques used interviews and documentation. The results showed that the application of the Problem Based Learning (PBL) learning model could improve the HOTS skills of fifth grade students starting from pre-action by 33%, cycle I by 50% in cycle II increased to 83%. The conclusion of this research is the application of the Problem Based Learning learning model (PBL) can increase HOTS in learning the theme 2 of animal locomotion in class V SDN 3 Sangub.